INFLUENCE OF INITIAL DENSITY ON BIOMASS PRODUCTION IN A Pinus taeda L. PLANTATION IN THE CENTRAL-SOUTH REGION OF PARANÁ, BRAZIL - do Vale, Aline Beatriz; Figueiredo Filho, Afonso; Guimarães, Fabiane Aparecida Retslaff; Karasinski, Mauro Alessandro (Floresta, 2022)
The evaluation of the productive potential of a forest plantation through biomass production is fundamental for managing and planning forest-based industries, with the spacing one of the factors that has influence on biomass production. This study aimed to evaluate the production of aboveground biomass in Pinus taeda L. stands as a function of the spacing, in which three different stands (2.0 m x 2.0 m (smallest), 3.0 m x 2.0 m (medium) and 4.0 m x 2.0 m (larger)), implanted in the municipality of Irati, Paraná state, Brazil, were evaluated. Thus, 47, 43 and 46 trees (from the 3 different spacings) were sampled by the direct method, respectively, totaling 136 trees. Each tree was segmented into: stem, live branches, dead branches and needles. The F-test (ANOVA) and Tukey’s test was applied. For all individual components analyzed, the “larger” spacing accumulated more biomass than the “smallest” and “medium” spacings, being 34.5 and 14.9% higher for the individual total biomass, respectively. As for the production per hectare, the “smallest” spacing produced 36.0 and 20.2% more biomass than the “larger” and “medium” spacings, respectively, configuring itself as the most appropriate for the total biomass production. The “stem” component represented from 83.7 to 88.5% of the produced biomass, followed by “dead branches”, “live branches” and “needles”. Only the biomass for dead branches and needles were significantly influenced by spacing.